Forecasting inflation with thick models and neural networks - Paul McNelis; Peter McAdam (European Central Bank (ECB), 2004)
This paper applies linear and neural network-based “thick” models for forecasting inflation based on Phillips–curve formulations in the USA, Japan and the euro area. Thick models represent “trimmed mean” forecasts from several neural network models. They outperform the best performing linear models for “real-time” and “bootstrap” forecasts for service indices for the euro area, and do well, sometimes better, for the more general consumer and producer price indices across a variety of countries.
Keywords: C12; E31; 330; bootstrap; Neural Networks; Phillips Curves; real-time forecasting; Thick Models